English: Morally Relevant Theory of Mind, Ekspresi Emosi Orang Tua, dan Perilaku Bohong Prososial Anak - Kuntoro, Ike Anggraika; Nabila Aulia Herman; Inge Uli Wiswanti (Jurnal Ilmu Keluarga dan Konsumen, 2023)
Prosocial lying refers to deceptive behavior performed for the benefit of others, which children may sometimes engage in to maintain positive relationships with peers and others. This research aims to identify the role of morally relevant theory of mind (MoToM) and parental emotional expression on prosocial lying behavior among children aged 7–9 years. The participants consisted of 66 parent-child pairs selected through the convenience sampling technique. The assessment of prosocial lying and MoToM was conducted through behavioral testing. Child participants (M=101.91 months; SD=8.36) were tested individually using the disappointing gift paradigm protocol and the MoToM. Meanwhile, parents were requested to respond to the SEFQ inventory. The results of the hierarchical logistic regression analysis revealed a significant relationship between MoToM and prosocial lying behavior, even after children's age was statistically controlled (X2(2)=5.872, p<0.01). In contrast, no significant influence was observed concerning parental emotional expression and children's prosocial lying behavior. This study highlighted insights on the relationship between MoToM and prosocial lying behavior, revealing that understanding MoToM is an influential factor in prosocial lying. Children should understand moral judgment and the impact of their behavior on others before engaging in prosocial lying.